2017
DOI: 10.12659/msm.905431
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Bowel Preparation Regimen for Colonoscopy Providing the Patients’ Satisfaction and Convenience

Abstract: BackgroundA complete cleansing of the bowel is a critical factor that impacts the diagnostic accuracy of colonoscopies. However, the common bowel preparation regimen of two 45 mL doses of sodium phosphate (2×NaP) often leads to uncomfortable symptoms and subsequently lower patient adherence. To improve patient adherence and satisfaction, we proposed a modified regimen composed of two sennoside tablets and one bottle of NaP (S+NaP) and we then evaluated bowel preparation quality and patient satisfaction.Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Patients understood the significance of bowel preparation, and engaged with appropriate methods and self‐assessment of the results. Patient compliance was improved, which is promising for the outcomes of colonoscopy 21 . The PP analysis showed that patients in the E‐reminder group had high subjective efficacy and satisfaction with automated phone and text message reminder services.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Patients understood the significance of bowel preparation, and engaged with appropriate methods and self‐assessment of the results. Patient compliance was improved, which is promising for the outcomes of colonoscopy 21 . The PP analysis showed that patients in the E‐reminder group had high subjective efficacy and satisfaction with automated phone and text message reminder services.…”
Section: Discussionmentioning
confidence: 91%
“…Patient compliance was improved, which is promising for the outcomes of colonoscopy. 21 The PP analysis showed that patients in the E-reminder group had high subjective efficacy and satisfaction with automated phone and text message reminder services. Thus, preoperative education was conducive to appropriate secondary bowel cleansing.…”
Section: Discussionmentioning
confidence: 97%
“…There are numerous studies focusing their effort to improve patient satisfaction, tolerance and receptiveness of bowel preparation through the selection of the agent, adjustment of volume required and its frequency. [19][20][21][22] Instead, when evaluating the results from a socioecological modelling perspective, our findings suggest that the network around these FIT-positive individuals play a huge role. Family members and close friends are likely to be able to persuade these individuals to complete the colonoscopic evaluation.…”
Section: Discussionmentioning
confidence: 94%
“…There are numerous studies focusing their effort to improve patient satisfaction, tolerance and receptiveness of bowel preparation through the selection of the agent, adjustment of volume required and its frequency. 19 , 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, improving the flavor of laxatives and reducing adverse effects is critical for qualified bowel preparation (4).…”
Section: Introductionmentioning
confidence: 99%